2019
DOI: 10.1002/prot.25644
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and accurate structure‐based therapeutic peptide design using GPU accelerated thermodynamic integration

Abstract: Peptide‐based therapeutics are an alternative to small molecule drugs as they offer superior specificity, lower toxicity, and easy synthesis. Here we present an approach that leverages the dramatic performance increase afforded by the recent arrival of GPU accelerated thermodynamic integration (TI). GPU TI facilitates very fast, highly accurate binding affinity optimization of peptides against therapeutic targets. We benchmarked TI predictions using published peptide binding optimization studies. Prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…A pre‐equilibrated structure tends to generate more stable ensembles and therefore more accurate estimations of the free energy (Garton et al, ). To that end, all water and ions atoms were removed from the structure with PDB code 1EKG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pre‐equilibrated structure tends to generate more stable ensembles and therefore more accurate estimations of the free energy (Garton et al, ). To that end, all water and ions atoms were removed from the structure with PDB code 1EKG.…”
Section: Methodsmentioning
confidence: 99%
“…Each simulation was repeated five times to calculate the ensemble-averaged values. More information on the recommended setup protocol found in the references (Garton et al, 2018;Lee et al, 2017;Seeliger & de Groot, 2010). Input files and scripts can be found here: https://gitlab.com/kimlab/rapid.…”
Section: Thermodynamic Integrationmentioning
confidence: 99%
“…Once a structural model of the complex is available both MD simulations and/or free energy calculations demonstrated that they can significantly contribute to design peptide modifications that results in an improved affinity and selectivity [61,62]. In particular, starting from the assumption that a significant increment of the affinity for the target would result also in an augmented selectivity, multiple methodologies with different degree of complexity such as thermodynamic integration or free energy perturbation [63,64] metadynamics [65,66], MM-GB(PB)SA [5,67,68] aimed to estimate the binding free energy (∆G) computationally, have been applied to evaluate which peptide modifications could result in a more favorable (more negative) binding energy. Additionally, in this case, literature reports some interesting examples about the use of computer simulations in the design of anticancer peptides, therefore we selected some of them to give to the reader a flavor of the impact that computer simulation had on this research field in the last ten years.…”
Section: Computational Design Of Anticancer Peptidesmentioning
confidence: 99%
“…Depending on computing resources, CMDboltzmann can be used to further and more accurately prioritize 100s to 1000s of the sequences of greatest interest. Indeed, the results of these calculations could be used to prioritize further synthesis or could be used for more computationally expensive methods such as molecular dynamics [21,22], free energy perturbation [23,24] or thermodynamic integration [25,26].…”
Section: Prospective Studymentioning
confidence: 99%